2005
DOI: 10.1016/j.rse.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenological dates in boreal regions using normalized difference water index

Abstract: Monitoring and understanding plant phenology are important in the context of studies of terrestrial productivity and global change. Vegetation phenology, such as dates of onsets of greening up and leaf senescence, has been determined by remote sensing using mainly the normalized difference vegetation index (NDVI). In boreal regions, the results suffer from significant uncertainties because of the effect of snow on NDVI. In this paper, SPOT VEGETATION S10 data over Siberia have been analysed to define a more ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
261
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(268 citation statements)
references
References 37 publications
4
261
0
3
Order By: Relevance
“…Therefore, NDVI cannot clearly discriminate the growing period from other conditions with a simple site-independent single threshold. We must consider the presence or absence of snow/water cover and understory vegetation for each target when we use NDVI, as pointed out by several studies [24][25][26][27]. Furthermore, as Nagai et al [13] have reported, the canopy condition of autumn coloring corresponded to different NDVI values from year to year.…”
Section: Applicability Of Grvi As An Indicator Of Vegetation Phenologymentioning
confidence: 99%
“…Therefore, NDVI cannot clearly discriminate the growing period from other conditions with a simple site-independent single threshold. We must consider the presence or absence of snow/water cover and understory vegetation for each target when we use NDVI, as pointed out by several studies [24][25][26][27]. Furthermore, as Nagai et al [13] have reported, the canopy condition of autumn coloring corresponded to different NDVI values from year to year.…”
Section: Applicability Of Grvi As An Indicator Of Vegetation Phenologymentioning
confidence: 99%
“…The graphs reflect correspondence between the ground and satellite observations. Some authors describe a possibility of allocation of the framing dates for full growing season through the allocation of the two corresponding minimums on the graphs (Delbart et al, 2005;Sekhon et al, 2010;Semenova, 2015). However, their publications are not cover the issue of separation of the full growing season into spring, summer and autumn.…”
Section: Analysis Of the Graphsmentioning
confidence: 99%
“…To reduce snow contamination, which generally results in a dramatically steep drop in NDVI and irregular variation in EVI , snow cover observations are explicitly removed or replaced. This is done using nearest non-snow observations in a temporal VI trajectory after winter periods are determined using ancillary data of land surface temperature and snow detection (Zhang et al, 2004a;Tan et al, 2011) or high values of NDWI (Delbart et al, 2005).…”
Section: Algorithm Of Phenology Detectionmentioning
confidence: 99%
“…The commonly used methods are the threshold-based technique which is divided into absolute VI threshold (e.g., Lloyd, 1990;Fischer, 1994;Myneni et al, 1997;Zhou et al, 2001) and relative threshold (e.g., White et al, 1997;Jonsson and Eklundh, 2002;Delbart et al, 2005;Karlsen et al, 2006;Dash et al, 2010), moving average (Reed et al, 1994), spectral analysis (Jakubauskas et al, 2001;Moody and Johnson, 2001), and inflection point estimation in the time series of vegetation indices (Moulin et al 1997;Zhang et al 2003;Tan et al, 2011). Various approaches in detecting phenological timing, particularly the greenup onset, are compared using the same dataset (de Beurs and Henebry, 2010;White et al, 2009).…”
Section: Algorithm Of Phenology Detectionmentioning
confidence: 99%
See 1 more Smart Citation